Unveiling the regioselective synthesis of antiviral 5-isoxazol-5-yl-2’-deoxyuridines from the perspective of a molecular electron density theory: Scientific paper - Acharjee, Nivedita; Mohammad-Salim, Haydar A.; Chakraborty, Mrinmoy (Journal of the Serbian Chemical Society, 2022)
The regioselective synthesis of a potent antiviral sugar nucleoside isoxazole analogue in the [3+2] cycloaddition (32CA) reaction of acetonitrile-N-oxide (ANO) and acetyl-protected 5-ethynyl-2’-deoxyuridine (EDU) has been studied at the MPWB1K/6-311G(d,p) level within perspective of the molecular electron density theory (MEDT). From an electron localization function (ELF) analysis, ANO is classified as a zwitterionic species devoid of any pseudoradical or carbenoid centre. The ortho regioisomer is energetically preferred over the meta one by the activation enthalpy of 21.7–24.3 kJ mol-1, suggesting complete regioselectivity in agreement with the experiment. The activation enthalpy increases from 53.9 kJ mol-1 in the gas phase to 71.5 kJ mol-1 in water, suggesting more facile reaction in low polar solvents. The minimal global electron density transfer (GEDT) at the TSs suggests non-polar character and the formation of new covalent bonds has not been started at the located TSs, showing non-covalent intermolecular interactions from an atoms-in-molecules (AIM) study and in the independent gradient model (IGM) isosurfaces. The AIM analysis shows more accumulation of electron density at the C–C interacting region relative to the C–O one, and earlier C–C bond formation is predicted from a bonding evolution theory (BET) study.